Shifting Harbor Seal ( Phoca vitulina ) Diet May Reflect Ecosystem Changes in Skagerrak - Foteini Kappa; Tero Härkönen; Carla Freitas; Daire Carroll; Karin C. Harding (Marine Mammal Science, 2026)
Harbor seals, as generalist predators, can adjust their diet in response to shifts in prey availability; thus, their diet composition has the potential to act as a biodiversity indicator. This study examined the diet of harbor seals in the Skagerrak by analyzing otoliths from scat samples collected in 2020 and compared species composition to historical datasets from 1977/78 and 1989. The diet in 2020 encompassed 28 fish species. Sandeel and Norway pout were the most common prey, comprising 39.6% and 21.8% of otoliths, respectively. The group haddock/pollack/saithe and ballan wrasse had the highest relative biomass contributions: 18.7% and 13.5%, respectively. A comparison with historical data revealed a shift in diet, with a notable decline in cod and herring consumption and an increase in sandeel and haddock/pollack/saithe. The findings suggest a dietary adaptation of harbor seals to available prey species. The reduced intake of energy‐rich prey like herring raises concerns about whether current diet composition can meet the seals' energetic needs. The observed dietary changes may reflect changes in prey availability due to environmental and anthropogenic factors, emphasizing the importance of continued studies to assess the implications for harbor seal populations in the region.